Ancaman resesi global pasca pandemi COVID-19 dan dampaknya terhadap ketahanan konsumen di Indonesia: Pendekatan analisis sintesis - Sudiro, Kania Lecya Kharima (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The COVID-19 pandemic has significantly impacted economic and consumer resilience in Indonesia, especially in facing the threat of a global recession. This research explores the relationship between the threat of a post-COVID-19 recession and consumer resilience. Through a qualitative approach with a literature study type and a synthetic analysis approach, this research analyzes 15 scientific works from 2007-2022 obtained from the Google Scholar database. The main findings include the potential threat of recession as indicated by the performance of high inflation reducing consumer purchasing power, declining economic growth in Indonesia -3.49% in 2020, and rising food prices triggering panic buying. Optimistic individual characteristics, adaptability, and financial literacy demonstrate consumer resilience. Preventive and collaborative strategies between government, business, and society are crucial to building strong consumer resilience.